Analisis Performa Quality of Service (QoS) pada Perancangan Surveillance Camera untuk Tujuan Kemanan - jafar, Nurul Aisyah (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
The rapid advancement of technology, such conditions can stimulate thinking and generate ideas to develop cutting-edge technology that benefits human life. One such application is in the field of security, supporting surveillance systems for the surrounding environment, such as parental monitoring of children in crowded places where loss of supervision may occur, as well as monitoring demonstrations. This study focuses on analyzing network quality in the design of an integrated surveillance camera system. In this research, the Wireshark software is used to assess network performance in the developed surveillance camera system. The results of the integration with the surveillance camera yielded Quality of Service (QoS) test results in both indoor and outdoor locations, where the average delay recorded in indoor conditions was 161.671 ms and 118.895 ms, and the packet loss value in both locations was 0%. Although certain locations exhibited signal loss, overall, the delay values in the outdoor tests were better compared to the indoor tests due to fewer obstacles in the outdoor environment.